Parasites, niche modification and the host microbiome: A field survey of multiple parasites. Issue 10 (12th April 2021) - O'Keeffe, Kayleigh R.; Halliday, Fletcher W.; Jones, Corbin D.; Carbone, Ignazio; Mitchell, Charles E.
Abstract: Parasites can affect and be affected by the host's microbiome, with consequences for host susceptibility, parasite transmission, and host and parasite fitness. Yet, two aspects of the relationship between parasite infection and host microbiota remain little understood: the nature of the relationship under field conditions, and how the relationship varies among parasites. To overcome these limitations, we performed a field survey of the within‐leaf fungal community in a tall fescue population. We investigated how diversity and composition of the fungal microbiome associate with natural infection by fungal parasites with different feeding strategies. A parasite's feeding strategy affects both parasite requirements of the host environment and parasite impacts on the host environment. We hypothesized that parasites that more strongly modify niches available within a host will be associated with greater changes in microbiome diversity and composition. Parasites with a feeding strategy that creates necrotic tissue to extract resources (necrotrophs) may not only have different niche requirements, but also act as particularly strong niche modifiers. Barcoded amplicon sequencing of the fungal ITS region revealed that leaf segments symptomatic of necrotrophs had lower fungal diversity and distinct composition compared to segments that were asymptomatic or symptomatic of other parasites. There were no clear differences in fungal diversity or composition between leaf segments that were asymptomatic and segments symptomatic of other parasite feeding strategies. Our results motivate future experimental work to test how the relationship between the microbiome and parasite infection is impacted by parasite feeding strategy and highlight the potential importance of parasite traits.